2016
DOI: 10.3389/fpsyg.2016.00501
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise As a Potential Way to Improve Self-Control after Ego-Depletion in Healthy Female College Students

Abstract: Purpose: To test whether aerobic exercise can help build self-control stamina in healthy female young adults. Stamina in this context is defined as the capability to endure ego depletion, which can be measured with a self-control task following another activity also requiring self-control.Methods: Forty-five healthy undergraduate women were randomized to either an experimental group or control group. Participants in the experimental group were required to run in their campus running field for 30 min for a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…To date, limited research has investigated whether physical activity can improve self-control. Zou et al (2016) found that five weeks of aerobic exercise could be a potentially effective intervention to improve self-control in college students. The authors assert that through low-intensity but regular exercise, individuals can train and enhance their self-control.…”
Section: Physical Activity and Self-controlmentioning
confidence: 99%
“…To date, limited research has investigated whether physical activity can improve self-control. Zou et al (2016) found that five weeks of aerobic exercise could be a potentially effective intervention to improve self-control in college students. The authors assert that through low-intensity but regular exercise, individuals can train and enhance their self-control.…”
Section: Physical Activity and Self-controlmentioning
confidence: 99%
“…One big advantage of such trainings may be the high domain-general capacity; training in self-control in one field may lead to broad improvements in other fields over time. For example, Zou et al (2016) have found that participating in 5 weeks of aerobic exercise (physical self-control) can increase self-control after ego-depletion in terms of pain tolerance. These pieces of evidence give reason to assume that adolescents low in self-control could benefit from exercise training, leading them to reduced problematic smartphone use.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…For example, people require self-control capacity to override the impulse to engage in a deviant act in pursuit of a higher-order goal, such as the goal to align one’s behavior with social expectations of ethical conduct. Self-control capacity can be enhanced over time through regular successful exertions of self-control (Baumeister et al, 1998, 2007), and physical activity represents one major domain in life in which such self-control is required and can therefore be developed (Oaten & Cheng, 2006; Zou et al, 2016). We argue that physically fit individuals are, on average, less likely to experience ego depletion, and hence more able to override their impulses to engage in deviant behaviors.…”
mentioning
confidence: 99%